GAMBARAN TINGKAT KECEMASAN DAN PENYEBAB KECEMASAN IBU HAMIL DALAM MELAKUKAN KUNJUNGAN ANTENATAL CARE DI PUSKESMAS PADA MASA PANDEMI COVID-19 - Anisa Fitadaris; Erika Erika; Veny Elita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
The COVID-19 pandemic makes pregnant women experience anxiety, especially in conducting pregnancy examinations. This study aims to identify an overview of the level of anxiety and causes of anxiety of pregnant women in conducting antenatal care visits in puskesmas during the COVID-19 pandemic. Method: The instruments used are the Zung SelfTwig Anxiety Scale (ZSAS/SRAS) questionnaire, the anxiety-causing questionnaire with a validity value of 0.468-0.650 > r table (0.444) and a family support questionnaire with a validity value of r calculated 0.500-0.789 > r table (0.444). Results: Of the 91 respondents, the majority of mothers experienced mild anxiety levels, amounting to 68 respondents (74.7%). Pregnant women who experience anxiety during the COVID-19 pandemic are mothers who are afraid of contracting COVID-19 from other patients (84.6%) and from health workers (87.9%), at the age of pregnancy in the second trimester of the mother who experience mild anxiety (80.6%), based on good family support in mild anxiety levels (79.7%) and based on a low economy with mild anxiety levels (75.0%). Conclusion: The anxiety of pregnant women in antenatal care during the COVID-19 pandemic is categorized with mild anxiety and causes of anxiety with high categories of mothers afraid of contracting COVID19 from medical personnel. Advice: This study is expected so that pregnant women's anxiety in conducting pregnancy checks during the COVID-19 pandemic, mothers can comply with health protocols so as not to contract COVID-19 both from others and from medical personnel.Keywords: Anxiety, antenatal care, COVID-19 pandemic, pregnant